PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DAN BELANJA MODAL PADA KELENGKAPAN PENGUNGKAPAN INFORMASI KEUANGAN DAERAH MELALUI SITUS RESMI PEMERINTAH PROVINSI - Dharma Jaya, Jeckly; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 9 No 1 (2014), 2014)
This study aims to examine the effect of local revenues (PAD), general fund allocations (DAU), and capital expenditures on the completeness of the disclosure of financial information through the official website of local provincial governments in Indonesia. This study uses a sample of 32 provincial governments with 96 observations obtained using purposive sampling method. The analysis technique used is a binary logistic regression. The results show that the local revenue and capital expenditure have significant positive effect on the completeness of the disclosure of financial information through the official website of local provincial governments in Indonesia, while the general fund allocations does not affect the completeness of the disclosure of financial information through the official website of local provincial governments in Indonesia.
Keywords: completeness disclosure of financial information, PAD, DAU, capital expenditure